Unequal smiles: consequences of untreated dental caries in citizens living in vulnerable circumstances in the Netherlands: an exploratory pilot study - Gitz, Sterre J.; Van der Heijden, Geert J.M.G.; M.C. Volgenant, Catherine (Acta odontologica Scandinavica, 2024)
The often poor oral health status of socioeconomically vulnerable adults is widely recognised. Nevertheless, research on it is scarce. To address this gap, this exploratory pilot study aimed to report on the prevalence of untreated caries and its clinical odontogenic consequences, as well as the associated Oral Health Related Quality of Life (OHRQoL) in a marginalised adult Dutch population. The Dutch department of Médecins du Monde (Doctors of the World) included socioeconomically vulnerable (low socioeconomic position [SEP]) adults in the Netherlands through community organisations. The validated Deprivation in Primary Care Questionnaire (DiPCare-Q) was translated in Dutch and used to characterise the SEP of the population. To document untreated caries and severe odontogenic consequences, the DMFT (Decayed, Missing, Filled Permanent Teeth) and PUFA (Pulpal, Fistula, Ulceration, Abscess) index were used. The validated Dutch Oral Health Impact Profile questionnaire (OHIP-14) was used to document the impact of these issues on OHRQoL. Data analysis was conducted in SPSS® (Statistical Package for the Social Sciences) statistics (Kruskal-Wallis, Mann-Whitney-U-test) and STATA software. Data from 59 adult participants were analysed. The prevalence of untreated caries (DT ≥ 1) was 65.5%, 57.9% of which experienced severe odontogenic consequences (DT+PUFA). The prevalence of severe odontogenic consequences (PUFA ≥ 1) was 45.5%. The mean OHIP-14 score of 17.7 ± 13.4 (25th–75th percentile: 6–26) illustrated that untreated caries may have impact on OHRQoL. Individuals who experienced any severe odontogenic consequences from untreated caries reported significantly higher OHIP-14 scores (mean ± s.d.: 21.8 ± 14.8 vs.11.1 ± 7.2). The untreated caries and severe odontogenic consequences seen in a large number of the socioeconomically vulnerable adult participants seemed to have an impact on OHRQoL. These findings emphasise the urgency of including these adults in the professional oral health system for treatment and prevention, and may emphasise the necessity of improving the socioeconomic circumstances of this population. Further exploration of the exact barriers and facilitators to oral healthcare access for socioeconomically vulnerable adults is necessary.